Impact of SARS-CoV2 infection on anti-apolipoprotein A-1 IgG response in inflammatory rheumatic diseases - Lamacchia, Celine; Mongin, Denis; Juillard, Catherine; Antinori-Malaspina, Paola; Gabay, Cem; Finckh, Axel; Pagano, Sabrina; Vuilleumier, Nicolas (Frontiers in Immunology, 2023)
Objectives: To investigate the impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infection on anti-Apolipoprotein A-1 IgG (AAA1) humoral response in immunosuppressed inflammatory rheumatic diseases (IRD) patients. Methods: This is a nested cohort study from the prospective Swiss Clinical Quality Management registry. 368 IRD patients for which serum samples were available before and after the SARS-CoV2 pandemic were included. Autoantibodies against ApoA-1 (AAA1) and its c-terminal region (AF3L1) were measured in both samples. The exposure of interest was anti-SARS-CoV2 spike subunit 1 (S1) seropositivity measured in second sample. The effect of SARS-CoV2 infection (anti-S1 seropositivity) on becoming AAA1 or AF3L1 positive, and on the change of AAA1 or AF3L1 optical density (OD) between the two samples was tested with multivariable regressions. Results: Twelve out of 368 IRD patients seroconverted against S1. The proportion of patient becoming AF3L1 seropositive was significantly higher in anti-S1 positive patients, compared to anti-S1 negative patients (66.7% versus 21.6%, p=0.001). Adjusted logistic regression analyses indicated that anti-S1 seroconversion was associated with 7-fold increased risk of AFL1 seropositivity (Odds ratio: 7.4, 95% Confidence interval (95%CI):2.1-25.9), and predicted median increase in AF3L1 OD values (+0.17, 95%CI: 0.08-0.26). Conclusions: SARS-CoV2 infection is associated with a marked humoral response against the immunodominant c-terminal region of ApoA-1 in IRD patients. The possible clinical impact of AAA1 and AF3L1 antibodies on disease progression, cardiovascular complications or long COVID syndrome deserves future investigations.